Influence of Compaction Temperature on the Properties of Marshall Specimens - Ivica Androjić; Sanja Dimter (The Baltic Journal of Road and Bridge Engineering)
Compaction of hot mix asphalt is influenced by several factors; some related to the environment, some determined by mix and structural design and some by contractor during construction. The temperature of asphalt mixture has the biggest influence on the compaction of asphalt mixtures and their properties. The temperature of asphalt mixture affects viscosity of bitumen and achievement of the maximum density of asphalt mixture. This paper describes a laboratory study on the effects of different installation temperatures on the physico-mechanical properties of specimens of asphalt mixtures: stability, Marshall Quotient (stiffness), density, voids and voids filled with asphalt. By regression analysis of the test results the correlation of certain properties of asphalt mix and compaction temperatures was established. For all the models observed, the coefficients of determination are very high and indicate very solid links. The obtained research results indicate a pronounced effect of compaction temperature on each tested property of asphalt mix.